PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI BERBASIS PENDEKATAN LINGKUNGAN PADA MATERI KLASIFIKASI MAKHLUK HIDUP KELAS VII SMP - -, Efriza - (Pendidikan Biologi, 2014)
Curriculum was seen as one of element which is able to give significant contribution for quality developing process of student. In 2013 Curriculum which is used nowadays by the government give the handbook for the teacher and handbook for the student as material for studying without using LKS. Meanwhile LKS is one of studying material which is needed by the student to optimalize for involvement and the activeness of the student in studying. LKS which is in the school as indicator, the purpose of studying hasnât been systematic, and itâs not completed by colorful picture so that it canât interest the student. Related to that, itâs developed studying media like LKS in Living creature classification for class VII SMP. This research has purpose to know the validity and practicality LKS based environment approachment.This research is developing research which is used 4-D models which is consist of 4 levels, they are define (definition), design (Design), develop (develop), and disseminate. The define level consist of front analysis, student analysis, and task analysis. In design level is done the design of learning media like LKS in material classify living creature, then in develop level is done validity test by validation who is consist of 2 lectures, and 2 teachers of SMP N 12 Padang and also 1 teacher from SMP Muhammadiyah 6 Padang. The practicality test by 3 teachers and 32 students of class VII junior high school, meanwhile the disseminate is not done.The result of LKS validity based on environment approachment by validation show that this LKS in valid criteria is 85,43% is shown from variable. The result of LKS practicality based on environment approachment by the teacher show that LKS is more practice that 93,26% and the result show that very practice is 88,30% is shown in used, the advantage and also efficiency can be concluded the development of LKS based one environment approachment in living creature classification which is produced valid and very practice.